AKTIVITAS PENANGKAPAN RADIKAL 2-2’ DIFENIL-1-PIKRIL HIDRAZIL (DPPH) EKSTRAK ETANOLIK DAUN MENGKUDU (Morinda citrifolia L.), DAN BATANG BROTOWALI (Tinospora crispa L.), FRAKSI AIR SERTA FRAKSI AIR TERHIDROLISIS - Tatang Irianti; Andayana Puspitasari; Machwiyyah L.; Rabbani HR. (Faculty of Pharmacy, Universitas Gadjah Mada, 2015)
We have investigated the antiradical activity of ethanolic extract of mengkudu leaves (Morinda citrifolia L.) and brotowali stem (Tinospora crispa L.) using radical scavenging assay or DPPH radical. Thin layer chromatograms were also studied to estimate the group of compounds that have antiradical activity. The objective of this research was to compare the DPPH antiradical efficiency values of water fraction and acid hydrolyzed water fraction in both extracts. The radical scavenging IC50 value of ethanolic extract, water fraction, and hydrolised water fraction (one and thee hours) of mengkudu leaves were 75,65 µg/mL ; 98,68 µg/mL ; 36,27 µg/mL and 33,36 µg/mL respectively. The IC50 value for brotowali stem were 33.75 µg/mL, 52.29 μg/mL, 31.12 μg/mL and 18.26 μg/mL. The highest antiradical activity was the hydrolyzed water fraction three hour namely 200 µg/mL of this fraction was able to inhibit 33.12% and 18.26 μg/mL DPPH radicals.